2020
DOI: 10.3390/su12031238
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Dockless Bikeshare Usage: A Case Study of Beijing, China

Abstract: The rapid emergence of dockless bikeshare systems has had a considerable influence on individuals' daily mobility patterns. However, information is still limited regarding the role that sociodemographics, social environments, travel attitudes and the built environment play on the adoption and usage of dockless bikeshare systems. To gain insight into what influences individuals to start and continue to use dockless bikeshare systems, this study sets out to assess the influential factors that are related to indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 35 publications
2
13
0
Order By: Relevance
“…Lowincome workers showed little participation in the public bicycle sharing program due to its complexity and high cost of registration [55]. The same results were also found in a dockless bike share study, which revealed that dockless bikeshare was less popular among low-income groups [56].…”
Section: Uneven Access To Alternative Transport Optionssupporting
confidence: 54%
See 1 more Smart Citation
“…Lowincome workers showed little participation in the public bicycle sharing program due to its complexity and high cost of registration [55]. The same results were also found in a dockless bike share study, which revealed that dockless bikeshare was less popular among low-income groups [56].…”
Section: Uneven Access To Alternative Transport Optionssupporting
confidence: 54%
“…Access to private vehicles Cheng et al, 2013 [27]; Zhao, 2013 [28]; Feng et al, 2014 [42]; Zhao, 2014 [29]; Li and Zhao, 2015 [46]; Wang and Liu, 2015 [30]; Zhang and Man, 2015 [31]; Dai et al, 2016 [43]; Linn et al, 2016 [32]; Zhao and Li, 2016 [16]; Feng et al, 2017 [44]; Jiang et al, 2017 [33]; Wei and Pan, 2017 [34]; Guo et al, 2018 [35]; Liu et al, 2018 [47]; Zhao and Zhang, 2018 [41]; Li et al, 2019 [7]; Zhao and Bai, 2019 [40]; Zhao and Li, 2019 [36]; Du et al, 2020 [37]; Lau, 2020 [39]; Wu et al, 2020 [39] Alternative transport options Lau, 2013 [53]; Karki and Tao, 2016 [55]; Aizezi et al, 2017 [52]; Feng et al, 2017 [44]; Yu et al, 2019 [51]; Chen et al 2020 [56] Urban structure…”
Section: Causes Studiesmentioning
confidence: 99%
“…According to Daxue Consulting ( https://daxueconsulting.com/mobike‐and‐ofo‐bike‐sharing/ ) in Beijing, 93% of trips less than 5 km are quicker by bike or public transport than by car. Chen, van Lierop, and Ettema ( 2020 ) stated that approximately half of the population in Beijing were registered as dockless shared‐bike members in 2017, suggesting that this large user base and the easy access to shared bikes have made BSS data suitable for characterization of human mobility. Du and Cheng ( 2018 ) studied BSS travel patterns in Nanjing via limited questionnaires.…”
Section: Introductionmentioning
confidence: 99%
“…Lastly, having a supportive social environment fosters the adoption and usage of bike sharing ( Chen et al, 2020 , Wang et al,, 2018 ). The trendy status ( Bachand-Marleau et al, 2012 ), as well as seeing people using the system positively influence BSS use ( Fishman et al, 2012 ).…”
Section: Literature Reviewmentioning
confidence: 99%